Penal Laws of the Hawaiian Islands, 1897, Compiled From the Penal Code of 1869 and the Session Laws of 1870 to 1896 Inclusive 251 (1897), ch. 54 - (:unkn) unknown (General Publisher, 1896)
Prohibited the carry of any Bowie-knife, sword-cane, pistol, air-gun, slung-shot, or other deadly weapon if not authorized by law. Violators fined no less than ten but no more than thirty dollars and imprisonment in hard labor camps no less than fifteen days but not exceeding two months. Note: Hawaii did not become US territory until 1898.
--
Keywords: CARRY